If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7m = (m + -4) Reorder the terms: 7m = (-4 + m) Remove parenthesis around (-4 + m) 7m = -4 + m Solving 7m = -4 + m Solving for variable 'm'. Move all terms containing m to the left, all other terms to the right. Add '-1m' to each side of the equation. 7m + -1m = -4 + m + -1m Combine like terms: 7m + -1m = 6m 6m = -4 + m + -1m Combine like terms: m + -1m = 0 6m = -4 + 0 6m = -4 Divide each side by '6'. m = -0.6666666667 Simplifying m = -0.6666666667
| -3(4-a)=-6 | | S=1/5(65-5e) | | 5x-3+3x+45=90 | | 4x-18+90=180 | | y=(x+3)(x^2+25)(x^2-2x+10) | | -3(4-a)=-15 | | -2n-12=-6(2+6n) | | 96=15+9s | | 5x+6(-2+18)=157 | | 5(n+3)=3(2*n-1) | | 8y-3y=35 | | 5x+6(-2+18)=108 | | 4y=3x+C | | 63/w=9 | | 12x=5(8+2x) | | h=-2(t-1)-16t(t-1) | | XP+to=z | | 8m+10=50 | | 4(x-5)+6=2(2x-7) | | x*5+65=4*x | | 24+5h=89 | | 10x-3/12 | | X^2-9x-19/x-2 | | 2x-54=104 | | 2(x+3)+x+7=2(3x+9)+5(4-x)+3 | | 4(3x+8)=32 | | 9x+4=5x+2 | | -3(x-4)+5=-2z-2 | | 5x^4=20x^6 | | 10d+6-6d=22 | | -3(x+8)=-15 | | -5(2.5+x)=10 |